A Study on Acceptance Level of Management Faculty Members towards Transmedia Story Telling - arijit goswami Arijit; Bhavna Prajapati Bhavna (International Journal of Marketing & Human Resource Research, 2022)
This study is focused on looking into the acceptance level of the teachers relative to transmedia storytelling, views on the modification of reading tasks and activities through transmedia storytelling, and integration of transmedia storytelling in reading tasks and activities. This study focuses and limits only in describing the acceptance level of management faculty members as to transmedia storytelling and on knowing the teachers’ thoughts on modification of reading tasks and activities. The study used descriptive research design wherein the data were analyzed through a modified questionnaire on the level of acceptance. The results of the study show a positive acceptance of transmedia storytelling among management faculty members. Furthermore, it was emphasized that transmedia storytelling is a beneficial and educational strategy for teaching reading and integration should be done through adapting and designing various media platforms. This action research presented a new reading strategy for management teachers that can be used in teaching learning aimed for a contextualized and expanded teaching and learning of reading through a matrix that include selected and applicable reading texts with transmedia storytelling media platforms.